Application of two-dimensional correlation spectroscopy for monitoring the mechanism of reaction between phenyl glycidyl ether (PGE) and metaphenylene diamine (mPDA) - Hollock, Michael R. (Kansas State University, 2012)
The curing reaction for the amine epoxy resin system of phenyl glycidyl ether (PGE) with metaphenylene diamine (mPDA) was investigated using two-dimensional correlation spectroscopy in the near-infared region (2DNIR). Synchronous and asynchronous correlation maps were generated using 2Dshige© software. The characteristic NIR band assignments were made, including the identification of new peaks for the O-H combination band in the 4825-4750 cm[superscript]-1 region and the CH stretching vibration overtone at 6018 cm[superscript]-1. Finally, the data suggests the reaction proceeds as follows: the appearance of the OH groups and C-H backbone vibrations occurs before the primary amine reactions and epoxide rings disappear.
Keywords: 2DNIR; Near-infrared spectroscopy; 2D correlation analysis; Epoxy curing; Chemical Engineering (0542)